NEED ANALYSIS STUDY: CRITICAL THINKING DISPOSITION PROFILE OF SCIENCE CLASS STUDENT IN HIGH SCHOOL - E Emiliannur; Ida Hamidah; Ana Ratna Wulan (Universitas Negeri Padang, 2023)
Critical thinking is essential for individuals who make judgments in their daily life, be them students at school or adults in the work or family environment settings. The aimed of this study was to describe Critical Thinking Disposition (CTD) profile of science class student in high school. This is a mixed method research that emphasizes quantitative and qualitative data collection. In this study, qualitative data was embedded in the quantitative data collection process to support the research results. Students selected as samples in this study were determined by random sampling. The selected students were science students in high school. Students' CTD profiles data were obtained through questionnaires, observations, and interviews. CTD questionnaire using a Likert scale with five answer options. Data obtained from student response questionnaires were processed using descriptive statistics. Based on the results, the average score of students' CTD in general still needs to be improved in each indicator because no one has reached the high category, all of them are still in the low and medium categories. Especially in the indicators of inquisitiveness and self-confidence which obtained scores in the low category. While the open-mindedness indicator is the indicator with the highest score in the moderate category.